Modeling development effort in object-oriented systems using design properties. - Briand, L.C (IEEE Transactions on software engineering)
In the context of software cost estimation, system size is widely taken as a main driver of system development effort. However, other structural design properties, such as coupling, cohesion, and complexity, have been suggested as additional cost factors. Using effort data from an object-oriented development project, we empirically investigate the relationship between class size and the development effort for a class and what additional impact structural properties such as class coupling have on effort. The paper proposes a practical, repeatable, and accurate analysis procedure to investigate relationships between structural properties and development effort. Results indicate that fairly accurate predictions of class effort can be made based on simple measures of the class interface size alone (mean MREs below 30 percent). Effort predictions at the system level are even more accurate as, using Bootstrapping, the estimated 95 percent confidence interval for MREs is 3 to 23 percent. But, more sophisticated coupling and cohesion measures do not help to improve these predictions to a degree that would be practically significant. However, the use of hybrid models combining Poisson regression and CART regression trees clearly improves the accuracy of the models as compared to using Poisson regression alone